EDUKASI PROGRAM MINDFULL BREATHING EXERCISE UNTUK MENGATASI DEPRESI PADA REMAJA DI SMA MUHAMMADIYAH KOTA BARAT SURAKARTA - Arif Pristianto; Rehning Puji Hastuti; Fitrotul Aulia; Tessya Hadika Novitasari; Bernadine Felicia Isdya Putri; Cikiesa Ilham Faiz (Rafandha Press, 2023)
Depression is a state of low mood that can affect a person's thoughts, feelings, behavior, and sense of well-being. Usually, teenagers who have symptoms of depression complain of feeling uneasy, anxious, decreased ability to concentrate, and sleep disturbances. Therefore, education is needed in the form of Mindful Breathing Exercise which aims to provide information in an effort to overcome depressive disorders in adolescents. The implementation of this activity begins with conducting surveys, observations, interviews, and permits. Then proceed with planning and activity proposals. Prior to providing education, the severity of depression was measured using the Depression Severity Analysis (PHQ-9). Furthermore, a question and answer session was held to find out students' knowledge regarding depression and continued with the provision of education 2 times and sharing time. After 2 weeks of this activity taking place, the severity of depression was again measured using the Depression Severity Analysis (PHQ-9). The results are to determine the severity of depression in adolescents